Novel near-infrared II aggregation-induced emission dots for in vivo bioimaging. Issue 4 (20th November 2018) - Lin, Jiacheng; Zeng, Xiaodong; Xiao, Yuling; Tang, Lin; Nong, Jinxia; Liu, Yufang; Zhou, Hui; Ding, Bingbing; Xu, Fuchun; Tong, Hanxing; Deng, Zixin; Hong, Xuechuan
Abstract : Novel biocompatible NIR-II aggregation-induced emission dots are facilely assembled and used for NIR-II biomedical fluorescence imaging. Abstract : Near-infrared II fluorescence imaging holds great promise for in vivo imaging and imaging-guided surgery with deep penetration and high spatiotemporal resolution. However, most NIR-II aromatic luminophores suffer from the notorious aggregation-caused quenching (ACQ) effect in the aqueous solution, which largely hinders their biomedical application in vivo . In this study, the first NIR-II organic aggregation-induced emission (AIE) fluorophore (HLZ-BTED ), encapsulated as nanoparticles (HLZ-BTED dots) for in vivo biomedical imaging, was designed and synthesized. The NIR-II AIEHLZ-BTED dots showed high temporal resolution, high photostability, outstanding water-solubility and biocompatibility in vitro and in vivo . TheHLZ-BTED dots were further used for long-term breast tumor imaging and visualizing tumor-feeding blood vessels, long-term hind limb vasculature and incomplete hind limb ischemia. More importantly, as a proof-of-concept, this is the first time that non-invasive and real-time NIR-II imaging of the gastrointestinal tract in health and disease has been performed, making the AIE dots a promising tool for gastrointestinal (GI) tract research, such as understanding the healthy status of GI peristalsis, diagnosing and evaluating intestinal motility dysfunction, and assessing drug effects on intestinal obstruction.